Cutaneous Pseudolymphoma With Langerhans Cell Hyperplasia—A Rare Case With Clinical Presentation Mimicking Malignancy and Potential Diagnostic Pitfall. (December 2021) - Ye, Cian-Hao; Chen, Chih-Jung; Chang, Kung-Chao; Wu, Yu-Hung; Chen, Mei-Ling; Chiu, Tsu-Man
Abstract : Abstract: We describe a rare case of cutaneous pseudolymphoma with Langerhans cell hyperplasia. An 84-year-old female patient presented with erythematous and pernicious-looking plaques on her scalp that had been present for months. Histologically, lymphoid follicles consisting of mixed-type lymphocytes and Langerhans cells were aggregated focally. The diagnosis was verified by several immunohistochemical stains and by clinical evaluation. Skin lesions were steadily resolved with low-dose corticosteroid and hydroxychloroquine.